Post-rifting magmatism at the northern margin of the South China Sea: Evidenced by an ocean bottom seismometer experimentKey points - Lu Zhang; Chen Cai; Rui Gao (Earthquake Science)
Magmatism at continental margins is of great significance in understanding the continental rifting. We present a two-dimensional P-wave velocity model derived from an ocean bottom seismometer experiment, conducted across the middle northern continental margin of the South China Sea (SCS). The detailed velocity structures reveal significant heterogeneities extending from the continental shelf to the continent-ocean transition zone. The crust exhibits its greatest thickness below the continental shelf, measuring ∼23 km and gradually thins to ∼13 km at the distal margin. Furthermore, a narrow and distinct continent-ocean transition with only 40-km width is revealed. We also observe a high-velocity layer within the transition zone, reaching thickness of up to 4 km, characterized by P-wave velocities ranging from 7.0 km/s to 7.6 km/s in the lower crust. Based on the syn-rift melt generation using decompression melting model, we ascertain that syn-rift magmatism cannot fully account for the observed thick high-velocity layer. By integrating findings from previous geophysical and geochemical studies presenting extensive volcanic edifice on the seafloor at the northern margin, as well as ocean-island-basalt-type magmatic samples in the SCS area, we propose that post-rifting magmatism associated with the Hainan Plume may have influenced the formation of the high-velocity lower crust within the transition zone and the northern margin of the SCS can thus be recognized as magma-poor type margin.